On Stoic Cosmopolitanism - Konstantakos, Leonidas (Prometheus - Journal of Philosophy., 2015)
Martha Nussbaum gives a timely and interesting exhortation of Stoic ideals in Patriotism and Cosmopolitanism, but any implementation of these ancient ideals may have very serious consequences, as they certainly did in antiquity. Material consequences (loosely speaking) are not the purpose of a Stoic sage’s actions. Yet if prudence is to be the virtue for us that it was to our philosophical ancestors then, would-be Stoics are obligated to be very careful in making decisions for a cosmopolitan worldview, especially if we are to approach our future based on ideals over which even the ancients argued.